A study protocol to assess the feasibility of conducting an evaluation trial of the ADVANCE integrated intervention to address both substance use and intimate partner abuse perpetration to men in substance use treatment - Gail Gilchrist; Sabine Landau; Polly Radcliffe; Mary McMurran; Gene Feder; Caroline Easton; Steve Parrott; Sara Kirkpatrick; Juliet Henderson; Laura Potts; Danielle Stephens-Lewis; Amy Johnson; et al. (Pilot and Feasibility Studies, 2020)
Abstract Background Strong evidence exists that substance use is a contributory risk factor for intimate partner abuse (IPA) perpetration. Men in substance use treatment are more likely to perpetrate IPA than men from the general population. Despite this, referral pathways are lacking for this group. This trial will assess the feasibility of conducting an evaluation trial of a tailored integrated intervention to address substance use and IPA perpetration to men in substance use treatment. Methods/design ADVANCE is a multicentre, parallel-group individually randomised controlled feasibility trial, with a nested formative evaluation, comparing an integrated intervention to reduce IPA + substance use treatment as usual (TAU) to TAU only. One hundred and eight men who have perpetrated IPA in the past 12 months from community substance use treatment in London, the West Midlands, and the South West will be recruited. ADVANCE is a manualised intervention comprising 2–4 individual sessions (2 compulsory) with a keyworker to set goals, develop a personal safety plan and increase motivation and readiness, followed by a 12-session weekly group intervention delivered in substance use services. Men will be randomly allocated (ratio 1:1) to receive the ADVANCE intervention + TAU or TAU only. Men’s female (ex) partners will be invited to provide outcome data and offered support from integrated safety services (ISS). Regular case management meetings between substance use and ISS will manage risk. Outcome measures will be obtained at the end of the intervention (approximately 4 months post-randomisation) for all male and female participants. The main objective of this feasibility trial is to estimate parameters required for planning a definitive trial including rates of consent, recruitment, and follow-up by site and group allocation. Nested formative evaluation including focus groups and in-depth interviews will explore the intervention’s acceptability to participants, group facilitators, keyworkers and ISS workers. Secondary outcomes include substance use, IPA, mental health, self-management, health and social care service use, criminal justice contacts, and quality of life. Discussion Findings from this feasibility trial will inform the design of a multicentre randomised controlled trial evaluating the efficacy and cost-effectiveness of the ADVANCE intervention for reducing IPA and improving the well-being of female (ex)partners. Trial registration ISRCTN79435190 .